Studies on the Utilization of Indian Oil Sardine (Sardinella longiceps) for the Preparation of Fish Sausages: 1. Effect of Washing in Water on Meat Characteristics and Sausage Quality - C.N., Ravishankar; T.M.R., Setty; T.S., Shetty (Fishery Technology, 2025)
Effect of washing the mince from Indian oil sardine (Sardinella longiceps) with chilled water on the quality of sausages prepared from it was studied. Samples of meat were drawn at the end of each washing cycle for the analysis of phys1cal, chemical, microbiological and organoleptic characteristics. The sausages prepared from the meat samplcs after each wash were also analysed for the quality. Washing of meat for six times, with a suspension time of 15 min was found to be optimum in improving the meat charactenstics and the sausage quality.